Otosclerosis and stapes surgery: results of 141 surgeries - Cerejeira, Rui (2009)
Objectives: Stapes surgery for otosclerosis aims to restore the transmission function of the stapes in the oval window, which is compromised by otospongiosis/otosclerotic foci. The main goal of this study is to analyze the quality of the surgical treatment offered to the patients with otosclerosis in the ENT department of Coimbra University Hospitals (HUC), during a period of 6 years.Material and Methods: Retrospective study addressing clinical and surgical outcomes of 141 surgeries in 102 patients, between January, 1 of 2002 and December, 31 of 2007.Results: An air-bone gap closure was obtained in 72% of patients; a residual air-bone gap 20 dB was found in 93% of cases. Medium postoperative air-conduction gain was 20±15 dB. Ten patients of 48 complaining from tinnitus (21%) referred its disappearance after surgery.Conclusions: Surgical treatment for otosclerosis in HUC has similar results to other series in the international literature.